Desarrollo de un sistema de facturación electrónica y control de inventarios, para la empresa Corsystel de la ciudad de Loja. - Cárdenas Encalada, Jhoanna Jackeline, María Belén Espinoza Rojas (2016)
This final year project was developed in order to automate the process of billing and inventory control company CORSYSTEL, this automation is based on a system of electronic vouchers such as invoice and credit note issued to customers through an e-mail, also you can track inventory, record the receivables and payables, the closing and opening boxes and print reports purchases and sales. For the project made use of the Iconix methodology initially getting the system requirements, which allowed us to make a robust design using sequence diagrams and robustness modelamientos use case, description thereof class diagram, etc., thus facilitating the application coding PHP programming language is used, with CodeIgniter framework for coding as they are powerful technologies to create cross-platform applications; on the other hand they allow us to save money and time in the development of such applications. As for the client application use JavaScript as it is a programming language very rich and expressive that allowed us to make improvements to the user interface, and as for the connection to the Web server of SRI was done using threads with JAVA, to perform the reception, approval and notification of electronic vouchers such as invoice and credit note. Finally authorization to use the SRI test environment in order to verify the correct functionality of the system is requested.